2016
DOI: 10.1080/21645515.2016.1191719
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine down-regulates stability of Foxp3 protein via Stub1 in Treg cells

Abstract: Foxp3-expressing Treg cells have been well documented to provide immune regulation by promoting immune tolerance and suppressing immune over-reaction. Cimetidine (CIM), used to inhibit stomach acid secretion, has been reported to promote immune responses and suppress Treg cell function in several studies. However, the underlying mechanism is unknown. To investigate CIM effects on the suppressive function of Treg and Foxp3, here we used CIM to stimulate human CD4 C CD25 C Treg cells and Jurkat T cells and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…In line with our findings, Li X revealed that RU486‐induced abortion was partially due to the reduced Foxp3 . Cimetidine resulted in the downregulation of Foxp3 via E3 ligase Stub1‐mediated proteasomal degradation . We found that EL4 cells have shown a decrease in Foxp3 protein upon exposure to ESA.…”
Section: Discussionsupporting
confidence: 89%
“…In line with our findings, Li X revealed that RU486‐induced abortion was partially due to the reduced Foxp3 . Cimetidine resulted in the downregulation of Foxp3 via E3 ligase Stub1‐mediated proteasomal degradation . We found that EL4 cells have shown a decrease in Foxp3 protein upon exposure to ESA.…”
Section: Discussionsupporting
confidence: 89%
“…In some experiments, mice were provided with cimetidine (CMTD, 100 mg/kg·d) by means of intragastric administration for 7 days starting from the day of the final irradiation. It has been reported that CMTD has a radioprotective effect by antioxidation and immunomodulation 64,68,69 . All animal experiments were approved by the Animal Ethical Committee of Fudan University and all methods were carried out in accordance with the guidelines of animal welfare legislation.…”
Section: Methodsmentioning
confidence: 99%
“…Upon TCR stimulation, E3 ubiquitin ligase, Cbl-b, together with Stub1, targets Foxp3 for ubiquitylation and degradation; and a deficiency of Cbl-b can partially rescue defective development of thymic Treg cells in Cd28 −/− mice (140). Cimetidine (CIM) can promote immune responses, suppress Treg cell function via activation of PI3K-AKT-mTOR signaling and increase of Stub1-mediated degradation of Foxp3, respectively (141). As mentioned above, Foxp3 phosphorylation by NLK prevents its association with the STUB1 and increases Foxp3 protein stabilization (87).…”
Section: Post-translational Modifications Of Foxp3mentioning
confidence: 99%